(untitled) (Altre Modernità, 2018)
Fanfictions have become the most extended literary phenomenon online in the past few years. Internet allows writers to freely create and share their texts, as well as to get in touch with their readers, which produces a reciprocal relationship that benefits the author and influences the texts. However, this new appropriating literature implies some problematic questions, such as the difficulty to identify the author as an individual, and to understand his/her virtual birth process. This research critically analyzes the problems that the author of fanfiction raises, by using Foucault and Barthes’ theories for the relationship with the text, as well as Lacan’s theory when it comes about the birth and development of the figure of the author in online media.